Study of the 26Al(n, p)26Mg and 26Al(n, α)23Na reactions using the 27Al(p, p')27Al inelastic scattering reaction. Issue 1 (January 2016) - Benamara, S; de Séréville, N; Adsley, P; Laird, A M; Hammache, F; Stefan, I; Roussel, P; Ancelin, S; Assié, M; Barton, C; Coc, A; Diget, C; et al.
Abstract: 26 Al was the first cosmic radioactivity ever detected in the galaxy as well as one of the first extinct radioactivity observed in refractory phases of meteorites. Its nucleosynthesis in massive stars is still uncertain mainly due to the lack of nuclear information concerning the 26 Al(n, p) 26 Mg and 26 Al(n, α) 23 Na reactions. We report on a single and coincidence measurement of the 27 Al(p, p') 27 Al(p) 26 Mg and 27 Al(p, p') 27 Al(α) 23 Na reactions performed at the Orsay TANDEM facility aiming at the spectroscopy study of 27 Al above the neutron threshold. Fourteen states are observed for the first time within 350 keV above the 26 Al+n threshold.